New solitary wave solutions and stability analysis of the Benney-Luke and the Phi-4 equations in mathematical physics - Ghanbari, Behzad; İnç, Mustafa; Yusuf, Abdullahi; Baleanu, Dumitru (Amer Inst Mathematical Sciences-Aims, 2019)
In this paper, we present new solitary wave solutions for the Benney-Luke equation (BLE) and Phi-4 equation (PE). The new generalized rational function method (GERFM) is used to reach such solutions. Moreover, the stability for the governing equations is investigated via the aspect of linear stability analysis. It is proved that, both the governing equations are stable. We can also solve other nonlinear system of PDEs which are involve in mathematical physics and many other branches of physical sciences with the help of this new method.
Keywords: Benney-Luke equation; Phi-4 equation; GERFM; stability analysis